Control of Public Policies: An evaluation from the point of view of the Legislative Power, the Judicial Power and the Court of Auditors - Chudzij, Luísa Fófano (Revista Digital de Direito Administrativo, 2020)
The object of study is the control of Public Administration in the context of Public Policies. Its general objective is the analysis of the possibility of control of administrative acts, related to Public Policies, by the Legislative, Judiciary and Court of Auditors. The method used for the construction of the main textual ideas was the deductive method based on a bibliographical, jurisprudential and legislative research. An initial approach was taken on the modalities of control of the Public Administration to, later, detail the characteristics of legislative, judicial and technical control exercised by the Court of Auditors. It concludes, in the context of the policy cycle, that the idea of accountability is essential, because it presupposes control and transparency of the public act. Thus, all phases of the policy cycle must be observed, in special, the control and evaluation phase, because through that means it is possible to measure if Public Policies fulfill their purpose: to realize fundamental rights.